93.0k views
5 votes
Factor the expression over the complex numbers. x2+36 Enter your answer in the box.

the x2 is squared

User Luaan
by
5.2k points

2 Answers

3 votes

hope this help Answer:( x - 3i√2)(x + 3i√2)

solve x² + 18 = 0

x² = - 18 ⇒ x = ±√- 18 = ±3i√2

factors are ( x - (3i√2))(x - (-3i√2))

x² + 18 = (x - 3i√2)(x + 3i√2

Explanation:

User Sangimed
by
5.5k points
1 vote

Answer:


x^(2)+36=(x-6i)(x+6i)

Explanation:

The given expression is


x^(2)+36

It's understood that this expression is equal to zero


x^(2) +36=0

Now, we isolate the variable and then apply a squared root to each side of the equation


x^(2)=-36\\x=\±√(-36)

At this point, you'll find that the equation doesn't have solution in the real numbers, that is, all solutions are in the complex numbers. We need to add the imaginary number
i=√(-1) to continue


x=\±√(-36)\\x=\±√(36)i\\x=\±6i\\\\x_(1)=6i\\x_(2)=-6i

Now, representing these solution as factors, we would have


x-6i=0\\x+6i=0

Finally,


x^(2)+36=(x-6i)(x+6i)

User Alaa AbuZarifa
by
4.8k points